EVALUASI PENATAAN RUANG KERJA DI GEDUNG REKTORAT KAMPUS UPN VETERAN JAKARTA DALAM RANGKA MENCEGAH PENYEBARAN PENYAKIT PADA SITUASI MASA PANDEMI - Muhamad Rangga Faturohman, (2021)
Health is a focus that the companies need to consider to make their workplace safe for workers in the pandemic situation. Workspace arrangement is very important to maintain secure and comfort. The Minister of Health of the Republic of Indonesia has regulated the regulation for The COVID-19 in office buildings which is HK.01.07/MENKES/328/2020 and The Centers for Disease Control and Prevention (CDC) also made a recommedation regarding COVID-19 Employer Information for Office Buildings. This study uses a qulitative method with an observation approach and in-depth interviews. The total number of rooms observed was seven with a total of five informants. The results of this study are that all rooms have not implemented the regulation about maximizing spatial planning and the COVID-19 protocol. Protocols including floor management, six feet distances, the installation of posters, and physical barriers that have not been implemented. The transfer of rooms is not possible due to the lack of available space. It is hoped that the rector will pay more attention to the aspects of spatial planning in the UPN Veteran Jakarta Rectorate Building.